2019
DOI: 10.1159/000502112
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol Disrupts Intestinal Barriers Activating Gut-Liver-Axis: Effects on Intestinal Mucus and Vascular Barrier as Entry Sites

Abstract: Background: The gut-liver-axis presents the pathophysiological hallmark for multiple liver diseases and has been proposed to be modulated during stress and shock. Access to the gut-liver-axis needs crossing of the mucus and gut-vascular barrier. The role of β-adrenoreceptor-activation for both barriers has not been defined and is characterized here. Methods: Splanchnic β-adrenergic stimulation was achieved by chronic intraperitoneal application of isoproterenol via alzetpump in vivo. The intestinal permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Our Mdr1a KO mice showed a reduction in the number of goblet cells in the colon, as well as in the expression of Muc2 and Tff3 , which would contribute to an increase in the epithelial permeability of the colon [ 28 ]. Indeed, it has been described that a reduction in goblet cells and Muc2 would be associated with an increase in pathogenic bacteria in the mucus layer and a greater penetration of these microorganisms into the mucosa [ 29 ]. SDP supplementation did not improve goblet cell abundance in KO mice but did attenuate the decrease in Muc2 expression and maintained Tff3 expression at similar levels to those of healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…Our Mdr1a KO mice showed a reduction in the number of goblet cells in the colon, as well as in the expression of Muc2 and Tff3 , which would contribute to an increase in the epithelial permeability of the colon [ 28 ]. Indeed, it has been described that a reduction in goblet cells and Muc2 would be associated with an increase in pathogenic bacteria in the mucus layer and a greater penetration of these microorganisms into the mucosa [ 29 ]. SDP supplementation did not improve goblet cell abundance in KO mice but did attenuate the decrease in Muc2 expression and maintained Tff3 expression at similar levels to those of healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cholinergic system of the skin and mucous membranes seems to play a special role in the stability of the barrier, as chronic, long-term psychosocial stress can compromise the skin's barrier function by modulating nicotine receptors on epithelial cells ( Curtis et al, 2012 ). Psychosocial stress was also shown to disrupt the function of the intestinal barrier ( Barreau et al, 2007 ; Moussaoui et al, 2017 ) and in this context the agonists of the beta-adrenergic receptor and the neuropeptides corticotropin-releasing hormone (CRH) and substance P (SP) were found to enhance barrier permeability ( Keita et al, 2010 ; Sorribas et al, 2019 ), while mast cell stabilizers and neutralization of the neurotrophin nerve growth factor (NGF) were able to improve barrier function ( Barreau et al, 2007 ; Kritas et al, 2020 ).…”
Section: Lasting Psychosocial Stress Exposure Has a Negative Impact Omentioning
confidence: 99%
“… 41 Although the reason(s) for the discrepancy between this and prior studies and the report by Liao et al 41 are not clear, they may relate, at least in part, to differences in the technique for injecting ISO IP, which can lead to transient hypotension 42 and increased gut permeability. 43 In our early studies with this model, we observed that mice that did not resume normal locomotor activity and developed a hunched posture and ruffled for 3-7 days after ISO injection also lost body weight and developed profound lymphopenia, and were distinctly different biologically from mice that recovered rapidly following ISO injection. With refinements in the ISO injection technique, we observed that the majority of ISO-injected animals recovered completely, consistent with what has been observed in patients with stress-induced cardiomyopathy.…”
Section: Discussionmentioning
confidence: 94%